Characterization of a mouse model of sickle cell trait: parallels to human trait and a novel finding of cutaneous sensitization - Zappia, Katherine J. (Br J Haematol, 2017)
Sickle cell trait (SCT) has classically been categorized as a benign condition except in rare cases or upon exposure to severe physical conditions. However, several lines of evidence indicate that individuals with SCT are not always asymptomatic, and additional physiological changes and risks may remain unexplored. Here, we utilized mice harbouring one copy of normal human β globin and one copy of sickle human β globin as a model of SCT, to assess haematological, histopathological and somatosensory outcomes. We observed that SCT mice displayed renal and hepatic vascular congestion after exposure to hypoxia. Further, we observed that SCT mice displayed increased cold aversion as well as mechanical and heat sensitivity, though to a lesser degree than homozygous sickle cell disease mice. Notably, mechanical hypersensitivity increased following hypoxia and reoxygenation. Overall our findings suggest that SCT is not entirely benign, and further assessment of pain and cutaneous sensitization is warranted both in animal models and in clinical populations.